Original paper Efficacy and safety of electronic brachytherapy for superficial and nodular basal cell carcinoma - Ballester-Sánchez, Rosa; Pons-Llanas, Olga; Candela-Juan, Cristian; Celada-Alvarez, Francisco Javier; de Unamuno-Bustos, Blanca; Llavador-Ros, Margarita; Ballesta-Cuñat, Antonio; A. Barker, Christopher; Tormo-Micó, Alejandro; Botella-Estrada, Rafael; Perez-Calatayud, Jose (Journal of Contemporary Brachytherapy, 2015)
Purpose: Surface electronic brachytherapy (EBT) is an alternative radiotherapy solution to external beam electron radiotherapy and high-dose-rate radionuclide-based brachytherapy. In fact, it is also an alternative solution to surgery for a subgroup of patients. The objective of this work is to confirm the clinical efficacy, toxicity and cosmesis of a new EBT system, namely Esteya® in the treatment of nodular and superficial basal cell carcinoma (BCC). Material and methods: This is a prospective single-center, non-randomized pilot study to assess the efficacy and safety of EBT in nodular and superficial BCC using the Esteya® system. The study was conducted from June 2014 to February 2015. The follow up time was 6 months for all cases. Results: Twenty patients with 23 lesions were included. A complete response was documented in all lesions (100%). A low level of toxicity was observed after the 4th fraction in all cases. Erythema was the most frequent adverse event. Cosmesis was excellent, with more than 60% of cases without skin alteration and with subtle changes in the rest. Conclusions: Electronic brachytherapy with Esteya® appears to be an effective, simple, safe, and comfortable treatment for nodular and superficial BCC associated with excellent cosmesis. It could be a good choice for elderly patients, patients with contraindications for surgery (due to comorbidities or anticoagulant drugs) or patients where surgery would result in a more disfiguring outcome. A longer follow-up and more studies are needed to confirm these preliminary results.